Hodnocení finanční situace výrobního podniku a návrhy na její zlepšení - Startceva, Nadezhda (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce je zaměřena na zhodnocení finanční situace a posouzení finančního zdraví společnosti ABB, s.r.o. na základě ukazatelů finanční analýzy za zvolené období. Dle výsledků finanční analýzy budou identifikovány slabé stránky hospodaření podniku a navrhnuta případná opatření pro odstranění slabých a posílení silných stránek.

Bachelor thesis is focused on evaluation of a financial situation and assessment of a financial health of ABB Ltd. based on financial analysis indicators for the selected period. The weakest points of company management will be identified and some steps to exclude weak points and to strengthen strong ones will be proposed as a result of financial analysis.
Evaluation of the Financial Situation of the Manufacturing Company and Proposals to its Improvement
Keywords: finanční analýza; podnikové finance; aktiva; pasiva; rozvaha; výkaz zisku a ztrát; poměrové ukazatele; pohledávky; likvidita; financial analysis; corporate finance; assets; liabilities; balance sheet; profit and loss statement; ratio indicators; receivables; liquidity